Italien: Kleine Orte der Kaiserzeit - Neudecker, Richard (e-Forschungsberichte des DAI, 2023)
Based on the evidence of about 200 small villages populated from Augustan times to the end of the 3rd century BC the world of small to smallest rural settlements apart from the imperial urban culture is studied within a research project in settlement archaeology. Thereby the lebensraum of estimated 90 % of the population in antique Italy is conceived.